Measurements of ozone in the Antarctic region during August and September of 1987 - Starr, Walter L.; Vedder, James F. (1988)
Mixing ratios are presented for ozone in the austral polar atmosphere during Aug. and Sept. of 1987. Since the mid-1970's, there has been a continuing decrease in the total column abundance of ozone over Antarctica during the late winter and early spring. This reduction now amounts to about one-half of the historical October mean. The results presented are derived from an ultraviolet ozone photometer. The ER-2 aircraft carrying 14 instruments participated in a major effort to penetrate the region of depletion. Data were gathered between altitudes of 53 deg and 72 deg S at pressure altitudes up to 21 km in a series of 12 flights. Additional data were obtained between latitudes of 37 deg N and 53 deg S on the 3 flight legs required to reach Punta Arenas from Moffett Field, CA, and on the same return legs to Moffett Field. The observed ozone mixing ratios indicate the effects of chemistry as well as the effects of the stratospheric polar vortex. Examples of the distributions of ozone mixing ratios as a function of altitude, latitude, or a time and the relationships to temperature and other trace gases are presented.